Implikasi Keberadaan Goodwill Pada Laporan Keuangan (Manfaat dan Distorsi) - Illahi, Ilham; Sumarni, Nini; Harfandi (Shafin: Sharia Finance and Accounting Journal, 2024)
This article discusses the impact of goodwill on financial statements, focusing on its benefits and distortions. Goodwill, an intangible asset arising from acquisitions where the purchase price exceeds the fair value of identifiable assets, can have a positive impact on a company's financial statements by increasing its net assets or equity. However, despite its benefits, goodwill also raises concerns, particularly about the accuracy of the recorded value. The valuation of goodwill is often based on estimates and assumptions, which increases the risk of inaccuracies in its measurement. Through a qualitative literature review, this study finds that while goodwill impairment may cause investors and stakeholders to revise their expectations of future earnings and cash flows, it may also lead to managerial opportunism, thereby reducing its reliability. To mitigate such risks, companies can improve audit quality and implement effective corporate governance practices. Finally, this study provides valuable insights into the impact of goodwill on financial reporting practices.